The Development of Theoretical Study of Social Interpretation: Social Relations - Saputra, Deden Mula; Kurniawan, Agung (Lembaga Yasin AlSys, 2025)
This article explores the historical and epistemological development of social commentary (al-tafsīr adabī al-ijtimāʿī) within the Islamic scientific tradition and its relevance to addressing contemporary social issues. Grounded in the premise that the Qur'an offers comprehensive guidance for all dimensions of human life, the study traces the evolution of Qur'anic interpretation from a predominantly textual-linguistic paradigm to a more contextual and socially engaged approach. Employing a qualitative methodology within a literature study framework, the research analyzes seminal works such as Tafsir al-Manar, Fī Ẓilāl al-Qurʾān, Tafsir al-Azhar, and Tafsir al-Miṣbāḥ, alongside the intellectual contributions of scholars including Muḥammad ʿAbduh, Sayyid Quṭb, Fazlur Rahman, and M. Quraish Shihab. The study investigates the epistemological foundations of social commentary through key Islamic concepts such as maqāṣid al-sharīʿah, the principle of maṣlaḥah, and the Theory of Double Movement. It proposes a typology of social commentary comprising four interpretive orientations: reformist, revolutionary, contextual, and transformative. The findings demonstrate that social interpretation effectively integrates Qur'anic values with real-world societal contexts, offering a dynamic and responsive framework for engaging with modern challenges. As such, it serves as a viable model for fostering a just, inclusive, and ethically grounded society.